The quality of public finances and economic growth - Barrios, Salvador; Schaechter, Andrea; European Commission : Directorate-General for Economic and Financial Affairs (Brussels: Office for Infrastructure and Logistics in Brussels, 2008)
Improving the quality of public finances (QPF) has become a new focus for European policy makers. This focus is largely a response to preparing the European economies for the dual challenge of ageing populations and increased exposure to global competition. At the EU level, the Stability and Growth Pact and the Lisbon Strategy for Growth and Jobs provide, in principle, the appropriate tools for fostering a greater role of QPF in fiscal surveillance but this has not yet fully materialised in practice. This is partly because a broad-based conceptual framework on what makes up QPF has been missing. This paper attempts to close this gap by developing a multi-dimensional approach on QPF. Moreover, it reviews how EU Member States fare in each dimension and summarises empirical findings on the links between QPF and growth, including through a growth-accounting approach using discriminant analysis.
Economic Papers.